FITOREMEDIASI AIR TERCEMAR TEMBAGA (Cu) MENGGUANAKAN Salvinia molesta DAN Pistia stratiotes SERTA PENGARUHNYA TERHADAP PERTUMBUHAN TANAMAN Brassica rapa - Fatihah Baroroh; Eko Handayanto; Rony Irawanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Electroplating industry is one of the industries that produces liquid waste containing Cu. The discharge of the liquid waste directly dumped into the river can cause negative effects. This study was aimed to elucidate the effectiveness of aquatic plants of Salvinia molesta) and Pistia stratiotes) in lowering the content of Cu in water containing 2 ppm and 5 ppm Cu. The remediated water was then used to water Brassica rapa. Results showed that Pistia stratiotes was able to decrease Cu heavy metal at concentrations of 2 ppm by 94% and 5 ppm by 90%, but Pistia stratiotes plant was damaged in the form of chlorosis and necrosis in both concentrations. Salvinia molesta was able to reduce Cu heavy metal by 96% at concentrations of 2 ppm and 95% at 5 ppm with no plant damage. In addition, the phytoremediation treatment could affect water and soil pH values. Post-phytoremediation water application had no significant effect on the growth and yield of Brassica rapa plant. Brassica rapa plant was also able to accumulate Cu heavy metal in its root and canopy. The value of Cu heavy metal content in the root and canopy of Brassica rapa plant was above the Cu metal threshold in the vegetables. Brassica rapa was damaged in the leave of chlorosis and necrosis due to toxicity of Cu heavy metal.